Хмарні технології, балансування навантаження, трафіку - Новіченко, Є. О. (ХНУРЕ, 2023)
In recent years, cloud technologies have gained popularity both in the daily life of users and in business. This includes different methodologies, tools, and software and hardware. Thanks to the specified mechanisms, the user can implement tasks, goals or projects. The work is performed on a remote server, which allows you to avoid a lot of problems with saving information and configuring the infrastructure. Cloud technologies are a trend that will stay with us for a long time and will only gain momentum. After all, the cloud is not just a useful tool for storing data and performing calculations, it helps companies adapt to changes, the scale and dynamics of which are growing.